(untitled) (Punyawati Journal, 2026)
Hollywood Cinemas are knotted to capitalism and becoming part of western identity whereas Bollywood Cinema often showed middle-class national feelings. In this context, this study assessed political transition, structural challenge and institutional reform practices of Nepalese film history. This study used library based historical research design and my personal reflections to assess past events and present institutional developments practices. The study brought theoretical insights from neo-Marxist political economy, historical institutionalism and cultural institutionalism for interpreting research issues The study find that early Cinema appeared like something just for the upper class, not something everyone shared. After a moment, Cinema began showing outside the public places and it became part of the Nepalese society and culture. During the Panchayat era, there was a censorship, filmmakers had to be underhand, using stories from myths or social issues. After democratic era, Nepali Cinema got technical support from India and also started mounting investment by the private sectors. During Maoist insurgency, Cinema started focused on specific socio-cultural issues and reaching out globally through streaming platforms. During the second flight, Cinema started mixing commercial fun with independent work, regional stories with investment support of private sector. Local tales and social issues centered narratives diffused in global market that built national history of identity politics. The study concludes that history of Nepali Cinema has been shaping by instable politics, global industries and modernization. However, Nepal Film Development Board has been actively playing institutional advocacy role to change political economy of the film industry. It can perform better to generate national economy. Therefore, the federation needs to endorse new Film Act and get the pending laws passed right away. New Act must set up a clear framework for transparent foreign direct investment policy with attractive grants. Provincial governments need to make their own film policies to mobilize unique landscapes and culture. They need to set up provincial film offices, to help with local shooting, logistics, and grants for ethnographic narrations. Likewise, at municipal level, there is a need for rapid permitting system that is transparent and cheap for local shoots. They must offer token of grants to the producers and build community screening halls to celebrate local film festivals.